Economic and social policies in place to reduce poverty in Algeria - Oumelkhir Soufi (Social Empowerment Journal, 2020)
The phenomenon of poverty is one of the most frequently discussed issues in the political, economic and social arena in various countries of the world, and it is also one of the oldest dilemmas that societies suffer, through social and economic development frameworks. Algeria, like the third world countries, since its independence, the problem of poverty in it has remained on the list of socio-economic problems that has tried to treat or mitigate, by adopting multi-level policies but it is still in conflict with this problem, According the public authorities took the necessary measures to regulate the economic and social aspects, and with the beginning of the third millennium, Algeria began to pay great attention to social development and economic development. Therefore, this article represents an attempt to identify the most important policies and methods adopted by Algeria In the fight against poverty and the extent of its effectiveness in reducing the effects of poverty.